APPLICATION OF SOME TRAVELLING SALESMAN PROBLEM SEARCH METHODS ON COMMERCIAL FLIGHT ROUTES WITH MAINTENANCE CONSIDERATION - Hudori, Musadad
The cost of airplane fuel is one of the important considerations for an airline in determining the price of its flight ticket. The increase in aviation fuel prices has the potential to cause an increase in flight ticket prices. In addition, airlines also need to consider the schedule and place of aircraft maintenance. Aircraft maintenance carried out at the right time and place can save the duration and cost of aircraft maintenance. One solution that can be considered is choosing the optimal flight route. The definition of an optimal flight route is a flight route that has a minimum flight cost, maintenance cost and duration of maintenance. Airplane route selection is one of the applications of the Traveling Salesman Problem (TSP). TSP is an optimization problem to find the best route by visiting all cities once and returning to the initial city. This final project will discuss the selection of flight routes with several stages, namely data collection, mathematical model design, application of methods, program simulation and analysis of results. The methods used in this research are Brute Force, Held Karp, Genetic Algorithm and Nearest Neighbor. This final project aims to choose a flight route that has minimum flight costs, maintenance costs and duration of maintenance using the Brute Force, Held Karp, Genetic Algorithm and Nearest Neighbor methods and then compare them. However, the program created in this final project requires a long execution time, so improvements are still needed so that the program can run faster. The results of this study are expected to be useful for airline companies in choosing flight routes or can be considered when they want to increase the number of aircraft in their airline.